One-pot ultrasonic cavitational emulsification of phytosterols oleogel-based flavor emulsions and oil powder stabilized by natural saponin. (December 2021) - Chen, Xiao-Wei; Yin, Wen-Jun; Yang, Dan-Xia; Wan, Zhi-Li; Ma, Chuan-Guo; Yang, Xiao-Quan
Graphical abstract: Highlight: Phytosterols oleogel-based flavor emulsions was prepared by a one-pot ultrasonic emulsification. Natural triterpene saponin was used as a natural emulsifier for emulsion stabilization. Optimal acoustic parameters highly depend on emulsion properties. Flavor oil powder enrich phytosterols was produced by a subsequently spray-drying. Phytosterols oleogel-based flavor oil powder exhibit an excellent fluidity, redispersion and the low-crystallinity. Abstract: Phytosterols oleogel-based flavor emulsions were successfully fabricated for the first time using natural tea saponin as emulsifier and one-pot ultrasonic technique. The effects of ultrasonic time and power, surfactant concentration, and type of flavor oils ( e.g., orange, lemon and peppermint) on the emulsion droplet size were investigated. Submicron emulsions with a dispersed phase made by flavor oil (20 wt%) + phytosterol (4 wt%) were stabilized with 3 wt% saponin were obtained by applying an ultrasonic time of 5 min and ultrasonic power of 280 W. The natural tea saponin emulsions exhibited a superior stability and encapsulation efficiency of phytosterol, compared to traditional emulsifiers. Flavor oil-phytosterol enriched powders were prepared by spray-drying and characterized by SEM, XRD and repose angle. The natural saponin encapsulated oil + phytosterol powders had excellent fluidity, redispersion behavior and low phytosterol crystallinity. It was demonstrated that ultrasound is an effective and suitable technique for fabricating fortified flavor emulsions and microcapsules, which may be used for developing functional lipids-based applications in the food, beverage and cosmetic industries.